Automated Reasoning 11th International Joint Conference, IJCAR 2022, Haifa, Israel, August 8-10, 2022, Proceedings - Blanchette, Jasmin; Kovács, Laura; Pattinson, Dirk (Lecture Notes in Artificial Intelligence,, 2022)
This is an open access book. It is available open access under a Creative Commons Attribution 4.0 International License via link.springer.com.